2013
DOI: 10.1111/trf.12340
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting umbilical cord blood stem cell suitability for transplantation in an in utero collection program

Abstract: Maternal, neonatal, and obstetric factors can all influence the acceptability of a cord blood unit collected in utero for banking. Furthermore, units with high TNC counts are more likely to be selected for banking. Identifying these variables in potential donors can likely increase the number of adequate collections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 16 publications
6
63
0
2
Order By: Relevance
“…The present study finding revealed a significant difference in the UCB volume and the TNC content produced by the primigravida and the multigravida; in favor to the primigravida women. Conversely, Keersmaekers et al, [7] found no significant power of the gravidity number on the obtained UCB volume and its cellular content in a study included 7,839 in utero collected UCB units at Michigan. This disagreement between the present study finding and that of Keersmaekers and colleagues could be related to the discrepancy between the subjects criteria.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study finding revealed a significant difference in the UCB volume and the TNC content produced by the primigravida and the multigravida; in favor to the primigravida women. Conversely, Keersmaekers et al, [7] found no significant power of the gravidity number on the obtained UCB volume and its cellular content in a study included 7,839 in utero collected UCB units at Michigan. This disagreement between the present study finding and that of Keersmaekers and colleagues could be related to the discrepancy between the subjects criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Keersmaekers et al (2014), had shown that the neonatal birth weight that met the TNC requirement was 3,503 ± 463 grams compared to 3,215 ± 453 grams for those that did not met the TNC requirement. [7] To calculate the sample size with precision/absolute error meet of 5% and type 1 error of 5%, the following formula was used: Sample size = [2 × (SD obtained from a previous study) 2 × (Z α/2 + Z β ) 2 ] / mean difference obtained from previous study. [11] Therefore, n = [2 × (463) 2 × (1.96 + 0.84) 2 ] / [3,503 -3,215] = 142.02.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 3 more Smart Citations